Neural representation of scale illusion: magnetoencephalographic study on the auditory illusion induced by distinctive tone sequences in the two ears. - Shinya Kuriki (Public Library of Science (PLoS), 2013)
The auditory illusory perception "scale illusion" occurs when a tone of ascending scale is presented in one ear, a tone of descending scale is presented simultaneously in the other ear, and vice versa. Most listeners hear illusory percepts of smooth pitch contours of the higher half of the scale in the right ear and the lower half in the left ear. Little is known about neural processes underlying the scale illusion. In this magnetoencephalographic study, we recorded steady-state responses to amplitude-modulated short tones having illusion-inducing pitch sequences, where the sound level of the modulated tones was manipulated to decrease monotonically with increase in pitch. The steady-state responses were decomposed into right- and left-sound components by means of separate modulation frequencies. It was found that the time course of the magnitude of response components of illusion-perceiving listeners was significantly correlated with smooth pitch contour of illusory percepts and that the time course of response components of stimulus-perceiving listeners was significantly correlated with discontinuous pitch contour of stimulus percepts in addition to the contour of illusory percepts. The results suggest that the percept of illusory pitch sequence was represented in the neural activity in or near the primary auditory cortex, i.e., the site of generation of auditory steady-state response, and that perception of scale illusion is maintained by automatic low-level processing.